Synthesis and investigation of the optical characteristics of RE3+ activated Ca2Li2Si2O7 (Rare earth = Eu, Tb) phosphor for W-LED application - Pragati Tale; Ashok Mistry; Bharti Bawanthade; Ashish Mathur; S.J. Dhoble (Chemical Physics Impact)
Novel Eu3+ and Tb3+ ions-doped Ca2Li2Si2O7 luminescent materials were prepared by a low-temperature solid-state reaction technique for LED application. The electronic transitions of 5D0 → 7F2 (Eu3+) and 5D4 → 7F5 (Tb3+) have caused the luminescent material to exhibit strong luminosity in 613 nm (red) and 545 nm (green), respectively. Fourier transform infrared (FT-IR) spectra were applied for the identification of functional groups, and powder X-ray diffraction (XRD) was used for structural analysis. Morphological data was gathered using scanning electron microscopy (SEM). Its color was also determined by calculating the CIE coordinates. The excitation, PL properties, and luminescence decay time of the emission transitions of Eu3+ (5D0 → 7F2) and Tb3+ (5D4 → 7F5) were measured in order to analyze luminosity spectra.